The Dog Owner's Handbook - Conn, Annette (London SevenOaks, 2006)
Suitable for dog owners, this book presents exercises, tips and practical advice, such as how to introduce a puppy to his new home, prevent attention-seeking behaviour, teach him to sit, lie down, stay and walk on a loose lead, give him the right amount and type, of exercise, and tips on diet and general good health.
Include Colors Illustration,Index
Keywords: Dogs -- Dogs--Health -- Dogs--Training